“I Kind of Want to Want”: Women Who Are Undecided About Becoming Mothers - Donath, Orna; Berkovitch, Nitza; Segal-Engelchin, Dorit (Frontiers in Psychology, 2022)
This study focuses on women who define themselves as being undecided about becoming mothers. It addresses the question of how these women navigate their lives between two main conflicting cultural directives and perceptions: pronatalism and familism entwined in perception of linear time on one hand; and individualism and its counterpart, the notion of flexible liquid society, on the other. The research is based on group meetings designated for these women, which were facilitated by the first author. Ten women participated in the study—of whom, most were heterosexual, half were single, and half were partnered. Data were collected using (1) questionnaires completed during individual interviews that preceded the group encounter; (2) transcripts of the discussions held during the ten group sessions; and (3) questions regarding the status of the women’s doubts about motherhood asked four years after participating in the group. Our findings expand the existing typology of women’s reproductive decision-making, and demonstrate how categories that are commonly perceived as binary intersect when one challenges the rigid classifications of “active decisions” and “passive decisions”; “motherhood” and “non-motherhood”, and “want to be a mother” and “don't want to be a mother”. The findings also suggest that after becoming mothers, women can change their maternal status from “non-mother” to “mother”, yet still continue to view themselves as indecisive regarding motherhood. Based on our findings, we will argue that while indecisiveness about motherhood derives from individualized neoliberal rhetoric, it simultaneously undermines that same rhetoric and contradicts the injunction to “know, to decide, to strive”. It opposes the expectation in post-feminist discourse, that women will make choices about their bodies and exert them, while also opposing the pronatalist rhetoric, and the temporal-linear discourse positing that women should “move forward” towards motherhood along with the ticking of the “biological clock”. Whereas some women sought to resolve their indecisiveness, other women found that the indecisiveness leaves all options open in a manner that expands their boundaries of autonomy in a society that seeks to limit it.